Pengaruh Penambahan Aspal Penetrasi 60/70 Dan Cairan Anti Rayap Terhadap Kinerja Perkerasan Daur Ulang AC-WC - M. Khoirun Rizal; Alfian Malik; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Asphalt and termite liquid are fluxing materials that can increase the strength of recycled asphalt pavement. This research reuses recycled materials to save on the use of asphalt and aggregate. The purpose of the study was to determine the Marshall characteristics of a mixture of worn-out asphalt concrete (AC-WC) on asphalt rejuvenation and termite antiliquid. This study used a mixture of each asphalt and anti-termite fluxing material with variations of 0.5%, 1%, 1.5%, and 2%. The research standard used the Marshall method according to the Bina Marga Specifications 2010 revision 3. Test results on asphalt-added material VMA, VFA values, stability and MQ have met specifications, VIM values are only at 1% variation with an average value of 3.67% that meets specifications, while the flow value does not meet the specifications and is too large with the highest value of 7.53%. The results of the anti-termite liquid additive test results are based on average values, only in 1% added ingredients that meet specifications based on Marshall Characteristics. VMA, VFA and Stability values of all variations have met the specifications and value of flow, VIM in variations of 0.5%, 1.5%, and 2% does not meet specifications while the MQ value is only for 0.5% added material does not meet Bina Marga 2010 specifications revision 3. The optimum level of added ingredients contains anti termite fluids with a variation of 1.4%, this variation is the mixture that is best used based on Bina Marga specifications 2010 revision 3. Keywords: Asphalt, termite liquid, AC-WC, Bina Marga Specifications 2010 Revision 3